Adsorção de corantes em óxidos mistos : estudos cinéticos, de equilíbrio e de reúso do adsorvente - Nascimento, Éricles Vale (2021)
The presence of dyes in the effluents is a serious problem and must be solved quickly as a means of environmental protection. Among all existing solutions, the unit operation of adsorption is one of the most interesting, as it uses small amounts of a solid material that has the ability of remove large amounts of the pollutant. With this in mind, this work performed the synthesis and characterization of mixed oxides with perovskite structure of LaxCa1-xMnO3 type (x = 0; 0,5 e 1,0) through the modified protein method, using collagen as a complexing agent for the structure and calcination at 700°C/2h, under 10°C.min-1 heating rate, aiming its application in the removal of the Bezaktiv Blue S-MAX commercial dye present in aqueous medium, with subsequent adsorbents regeneration and reuse for five more times. The XRD indicated that the perovskite phase was obtained for materials with x = 0,5 and 1,0, with high crystallinity and low/none secondary phase content. For CaMnO3, an amorphous mix of precursor, calcium and manganese oxides were obtained, with the perovskite phase formation just initiated. The three synthesized materials have a rough surface and particles of varying sizes. In addition, they have meso and macropores in the slit or cavity shape, with average diameter between 30 and 40 nm and specific surface area around 10 m2 /g. The successfully obtained oxides showed PZC around neutrality. The FTIR test showed that adsorption process is not destructive to the adsorbents. The dye showed mass absorptivity of 24,9 L.g-1 .cm-1 . The adsorption tests were carried out in batch mode, triplicate, in a single stage, with the solution pH corrected to 3,0, in which 20 mg of adsorbent in contact with 20 ml of dye solution were used in 10, 30 and 50 ppm initial concentrations, in contact times from 0 to 90 minutes, interspersed in 10 minutes. The experimental data were better suited to pseudo-second order kinetic model for all adsorbents and in practically all initial dye concentrations. For the LaMnO3, the Langmuir model best represented the adsorption equilibrium while for the other two adsorbents it was the Freundlich model. The materials regeneration was done by heating them in the same condition as calcination. The reuse study showed that LaMnO3 maintained its adsorptive capacity, La0,5Ca0,5MnO3 started to act as a catalyst and CaMnO3 had the formation of its structure consolidated. In general, the adsorbent that showed the best performance was the LaMnO3, due to the high removal percentages and for having kept its adsorptive capacity stable throughout the adsorption-regeneration cycles.